Optimization of Knowledge Management to achieve Competitive advantage in the Hospitality Industry - Kawiana, I Gede Putu (SEAN Institute, 2023)
This study discusses the importance of optimizing Knowledge Management (KM) in achieving competitive advantage in the hospitality industry. The highly dynamic and competitive hospitality industry requires a careful approach in managing and utilizing knowledge effectively. The purpose of this research is to analyze how the implementation of KM strategy can improve service quality, operational efficiency, and differentiation in the hospitality industry . This research uses a qualitative approach with descriptive methods. Research findings reveal that aspects such as deep understanding of customers, strong relationships with stakeholders, accurate knowledge of products and services, and mastery of individual potential in organizations all play an important role in shaping unique experiences for customers, designing effective marketing strategies. , and create high-quality services. Through the implementation of an efficient KM system, hotels can combine this knowledge to win the competition in the dynamic hospitality industry.